Correlation Between Restorative Justice in the Settlement of Criminal Cases and Pancasila Values - Isma Septiningsih (Universitas Syiah Kuala, 2023)
The purpose of sentencing in this modern era has shifted to contemporary theory, which is directed to restorative justice. The embodiment of restorative justice in the criminal justice system can be obtained by bringing together the parties involved in a criminal case, to obtain an agreement in the settlement of criminal cases, and be oriented to the recovery of victims' losses. Looking at the concept of restorative justice, it is clear that there are Pancasila values in it. Several regulations have accommodated the realization of restorative justice, one of which is Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Even though it has been regulated, the application of restorative justice in juvenile justice still has several shortcomings, for example the limitation of doing diversion. Studying the relationship between restorative justice and Pancasila, it was found that restorative justice aims to create social justice for all parties involved in a criminal case by means of deliberation to reach consensus.